From the results of the stability of soil structure studies and the physical characteristics of the black meadow soil of the mountain meadow in the limited national park (gorkhi-terelj national park) - B, Lkhamsuren; B, Odgerel; Sh, Purevsuren (Mongolian Journal of Agricultural Sciences, 2018)
The study aims to investigate changes in the physical properties of soil depending on the utilization conditions of the Special Protected National Park compared to the area fenced for more than 10 years. The stability and stabilization of the stabilized mountain meadow soil stabilization and physical properties of soil in the Gorkhi-Terelj National Park (GTNP) resort and limited concentration of tourism. As a result of the study, the stability of the soil structure was 2.8 points in the area of vegetation cover 0-3 cm outside the fence, while the 2.6 layered soil layers above the soils of the vegetation cover. However, the area with vegetation cover within the fence is 4.2 points in soil 0-3 cm and 4 leaves in soil without vegetation cover.